Valuation of Indonesian Cable Company with Free Cash Flow to Firm and Relative Valuation - Harjono, Sucipto; Hendrawan, Riko (International Journal Labs, 2023)
During 2014 - 2018, cable companies in Indonesia showed an 8.52% average annual revenue growth. Unfortunately, analysts are responding to this growth negatively. Hence, In this study, we will conduct a valuation of six cable companies in Indonesia that are listed on the Indonesia Stock Exchange (IDX). We evaluate using two methods, namely Free Cash Flow to Firm (FCFF) to get the Intrinsic Value of shares, Relative Valuation using Price to Book Value ( PBV), and Price to Earnings Ratio (PER) to validate the intrinsic value. The valuation results consider three scenarios: optimistic, moderate, and pessimistic. In the optimistic scenario, the Intrinsic Value of JECC, KBLI, and VOKS shares are overvalued in all scenarios, while IKBI, KBLM, and SCCO are undervalued throughout the scenario. Validation using PBV for the optimistic scenario, all companies are considered overvalued. For the moderate scenario, the PBV of IKBI, KBLI, and VOKS are overvalued, while JECC, KBLM, and SCCO are undervalued. As for the pessimistic scenario, only the PBV of IKBI is overvalued. Validation using PER for the optimistic scenario, the PER of IKBI, JECC, KBLM, and SCCO are overvalued, while the PER of KBLI and VOKS are undervalued. For the moderate scenarios, the PER of IKBI and SCCO are overvalued, while the PER of JECC, KBLI, KBLM, and VOKS are undervalued. Whereas for the pessimistic scenario, only the PER of IKBI is overvalued, while JECC, KBLI, KBLM, SCCO, and VOKS are undervalued.